Occupational Risk Factors and Preventive Measures for Covid 19 in Prosthodontics - Hamna Khawaja, Mehmood Ahmed Rana, Shoaib Alvi, Ayesha Sadaf, Shamima Abdullah, Amna Jalal (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The Aim of this study is to determine the occupational risk factors and preventive measure for Covid-19 in prosthodontics. Study Design:Cross-sectional study Place and Duration: Conducted at Nishtar institute of dentistry Multan during from the period 01 July, 2021 to 31 Dec, 2021 Methods: There were one hundred and thirteen professionals working in prosthodontics were presented in this study. Enrolled cases were aged between 22- 55 years. After obtaining informed written permission, the demographics of enrolled professionals were recorded, including age, sex, residence, occupation, and marital status.Association of risk factors in their occupation related to Covid-19 and its preventive measures were measured and calculated. Awareness of vaccine and vaccination status was also recorded. SPSS 24.0 was used to analyze all data. Results:Among 113 cases, majority of the cases were females 73 (61.3%) and rest were males 40 (38.7%). 45 (39.8%) cases were aged between 22-28 years, 40 (35.4%) were aged between 29-34 years and 28 (24.7%) had ages > 35 years. 63 (55.8%) were married and 78 (69.02%) had urban residency. Majority were dentist 85 (75.2%) and 20 (17.7%) were dental assistants and 8 (7.1%)are dental technicians .64 (56.6%) were vaccinated and 40 (35.4%) were partially vaccinated.Most common symptoms were fever, cough, fatigue and shortness of breath. Risk factors were direct contact, not used of personal protective equipment (PPE) or lack of PPE i.e. gloves, hand wash, sanitizer and mask. Instantly change of gloves, hygienic cleaning, change of dress after job hours and social distance were the preventive measures. Conclusion: Given the pathways of COVID-19 transmission, even dental practitioners must adjust usual methods to avoid infection. In clinical conditions, dentists must recognize the signs and symptoms and perform stringent infection control.